Human Resources Development Model to Improve Educator and Educational Quality - Rustamin, Rustamin (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
The development model is the basis and main which is very important in an educational institution. Therefore in determining the development model must be right on target. The aim of this research is to find out the right model of human resource development in improving the quality of teaching and educational staff at the Ar-Rachmat Foundation. The research method used and data processing is qualitative in nature, to obtain qualitative data it is carried out using FGD (Focus Group Discussion) with the SWOT analysis method. The results of the SWOT analysis are the strategic model of human resource development in increasing teaching and educational staff, namely using the Offensive Growth Strategy. The growth of an offensive strategy is a strategy that continues to develop and find existing opportunities which will later become a source of strength in utilizing competitors in achieving goals.